Inoculation of mycorrhizal fungi on a vineyard. The impact of a mycorrhiza-inoculated under-vine cover crop on grapevine performance and soil quality in a Portuguese vineyard - Ervedeiro, João Maria da Gama Pinto Magalhães (2022)
Mestrado em Engenharia Agronómica / Instituto Superior de Agronomia. Universidade de Lisboa